(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Objectives: This study aimed to evaluate the potential efficacy and safety of Dr. Ortho capsules in managing various musculoskeletal conditions, including knee pain, joint stiffness, arthritis, bulky shoulders, joint inflammation, acute sports injuries, strains, and sprains. Methods: The study was a single centric, open-label, non-randomized, post-marketing surveillance study involving 120 subjects. Subjects were selected based on inclusion and exclusion criteria. The study assessed changes in pain intensity and disability levels after the administration of Dr. Ortho capsules, employing the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI), respectively. Additionally, safety was evaluated through physical examinations, vital sign monitoring, and laboratory safety parameters. Results: The study revealed significant reductions in pain intensity and disability levels among the participants. Pain intensity, as measured by VAS, decreased significantly (p< 0.0001) from a mean score of 4.84 at baseline (day 1) to 0.38 at the end of the study (day 30). Disability levels, indicated by ODI, significantly improved (p<0.0001) from a mean score of 14.73% at baseline to 1.88% at the end of the study. There were no reported adverse events during the study, and all safety parameters remained within normal ranges. Conclusion: The findings of the study suggest that Dr. Ortho capsules may offer effective relief for individuals with musculoskeletal conditions, reducing pain intensity and improving functional abilities. The absence of adverse events and the maintenance of normal safety parameters indicate the safety of Dr. Ortho capsules for human consumption.